INTEGRASI LITERASI SYARIAH DAN LITERASI FINTECH DALAM POLA PENGELOLAAN KEUANGAN SEBUAH TINJAUAN PSIKOLOGIS KONTROL DIRI - Balya, Toifur Ahmad; Mustofa (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2026)
This study aims to examine the effects of Digital Financial Literacy (DFL) and Islamic Financial Literacy (LKS) on Islamic Financial Management (MKS), as well as the mediating role of Self-Control (S-C) among university students. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS‑SEM) for data analysis. The results indicate that both DFL and LKS have positive and significant impacts on MKS, directly and indirectly through S-C. Self-Control is shown to mediate the relationship between financial literacy and Islamic financial management, suggesting that students’ ability to control impulsive behavior is crucial in translating financial literacy into effective financial management practices. These findings align with the Theory of Planned Behavior (TPB) and Self-Control Theory, supporting existing literature on financial literacy, fintech adoption, and Islamic financial management. The study highlights the importance of integrating digital literacy, Islamic financial literacy, and self-control to foster ethical, rational, and sharia-compliant financial behavior in the digital era. Practical implications include the development of educational programs on digital and Islamic financial literacy, alongside interventions to enhance self-control as a strategy to improve students’ financial management skills.